Mapping out a Canadian university’s trauma-informed landscape: A preliminary exploration - Mélanie Letendre Jauniaux; Heather L. Lawford (Global Public Health)
Adversity and trauma are commonly misunderstood human experiences affecting most individuals across post-secondary campuses. Depending on contextual factors, they can lead to lifelong challenges or growth. Without an adequate understanding, well-meaning individuals and organisations may unknowingly perpetuate harm. Trauma-informed approaches (TIAs) can help organisations prevent harm, promote empowerment, and enhance connection. Preliminary investigations are critical for the development of sustainable TIAs. This exploratory study investigated the attitudes, knowledge, and workplace culture concerning adversity and trauma at a small Canadian university with no existing TIA. The study involved two phases: first, preliminary consultations with ten community stakeholders and a review of relevant literature, and second, nine semi-structured interviews with staff and faculty, followed by reflexive thematic analysis of the data. Four key themes emerged: (1) limited trauma awareness on campus, highlighting a need for system-wide training and tools, (2) privilege and vulnerability, disparities in safety, flexibility and agency across university departments, (3) pockets of safety, academic culture and other barriers to change, (4) suggestions to address barriers, through trauma education, human-centric practices, and systemic collaboration. This study provides insight into the readiness, challenges, and recommendations for developing system-wide trauma awareness in a Canadian university.